Stillbirth in Lao PDR: a healthcare provider perspective. Issue 2 (30th July 2020) - Choummanivong, Molina; Karimi, Sediqa; Durham, Joanne; Sychareun, Vanphanom; Flenady, Vicki; Horey, Dell; Boyle, Fran
ABSTRACT: Background: Stillbirth is a major global concern. However, most research has been conducted in high-income countries. Understanding of the experience and management of stillbirth in low-middle income countries is needed. Objective: This qualitative study explored health professionals' experiences of providing stillbirth care in the Lao People's Democratic Republic, a lower-middle-income country in South-East Asia. Methods: In-depth interviews were conducted with 33 health professionals (doctors, midwives and nurses) and thematic analysis was undertaken. Results: All participants acknowledged stillbirth as a concern, but its incidence and causes were largely undocumented and unknown. A lack of training in managing stillbirth left health professionals often ill-equipped to support mothers and provide responsive care. Social stigma surrounds stillbirth, meaning mothers found limited support or opportunities to openly express their grief. Conclusions: Better awareness of stillbirth causes could promote more positive experiences for healthcare providers and parents and more responsive healthcare. This requires improved training for healthcare professionals and awareness raising in the wider community.